To determine which equation fits the order of steps "to first divide both sides by 6 and then to add 8 to both sides," we can analyze each option.
-
For the equation 6(x − 8) = 48:
- Dividing both sides by 6: \( x - 8 = 8 \)
- Adding 8 to both sides: \( x = 16 \)
-
For the equation 8(x − 6) = 48:
- Dividing both sides by 8: \( x - 6 = 6 \)
- Adding 6 to both sides: \( x = 12 \) (This does not match as we divide by 8).
-
For the equation 6x − 8 = 48:
- Dividing both sides by 6: \( x - \frac{8}{6} = 8 \) (This is incorrect for dividing by 6 first).
- Adding 8 to both sides would not follow the definition either.
-
For the equation 6(x + 8) = 48:
- Dividing both sides by 6: \( x + 8 = 8 \)
- Adding 8 to both sides: \( x = 0 \) (same reasoning as above).
The correct choice is 6(x − 8) = 48, as this equation allows you to first divide both sides by 6 and then add 8 to both sides, the required steps.